To evaluate the use of ProSeal laryngeal mask airway in patients undergoing elective lower segment cesarean section under general anesthesia: A prospective randomized controlled study - Shalini Saini; Sharmila Ahuja; Kiran Guleria (Wolters Kluwer Medknow Publications, 2016)
Background: Anaesthesia for caesarean section poses challenges unique to the obstetric patient due to changes in the airway and respiratory system. The choice of anaesthesia for caesarean section depends on various factors; however, general anaesthesia (GA) is necessary in certain situations. Supraglottic airway devices are an emerging method to secure the airway, especially in difficult situations. Of these devices, ProSeal laryngeal mask airway (PLMA) is designed to provide better protection of the airway. Use of PLMA has been reported to be successful as a rescue device in difficult intubation situations and in patients undergoing elective caesarean section without any complications. Hence, this prospective randomized study was designed to compare the use of PLMA with endotracheal tube (ETT) in patients undergoing elective lower segment caesarean section (LSCS). Material and Methods: Patients undergoing LSCS under GA belonging to the American Society of Anaesthesiologists (ASA) grades 1 and 2 were included. Patients with history of less than 6 h of fasting, known/predicted difficult airway, obesity, gastro-esophageal reflux disease, and hypertensive disorder were excluded. A standard anaesthesia protocol was followed. All patients received aspiration prophylaxis. The airway was maintained with either PLMA or ETT. The parameters including ease of insertion, adequacy of ventilation, hemodynamic changes at insertion and removal of device, and incidence of regurgitation and aspiration were noted. Statistical analysis: The data were analyzed by unpaired t-test, chi-square/Fisher's test. Results: Findings of the study indicated that PLMA was easy to insert (20.67 ± 6.835 s) with comparable insertion time to ETT (18.33 ± 4.971, P = 0.136) and adequate ventilation was achieved with very minimal hemodynamic changes seen with PLMA as compared to ETT at the insertion and removal of devices (P = 0.01). There was no incidence of regurgitation with the use of PLMA. The incidence of postoperative sore throat was minimal (6.7%) with PLMA (P < 0.05). Conclusion: PLMA appears to be a safe alternative to ETT for selected obstetric patients undergoing elective LSCS. A further study with a large group of patients is required to establish the safety of PLMA in obstetric patients.